A Comprehensive Review of Endoscopic Management of Sleeve Gastrectomy Leaks. Issue 7 (August 2021) - Gjeorgjievski, Mihajlo; Imam, Zaid; Cappell, Mitchell S.; Jamil, Laith H.; Kahaleh, Michel
Abstract : Background: Bariatric surgery leaks result in significant morbidity and mortality. Experts report variable therapeutic approaches, without uniform guidelines or consensus. Objective: To review the pathogenesis, risk factors, prevention, and treatment of gastric sleeve leaks, with a focus on endoscopic approaches. In addition, the efficacy and success rates of different treatment modalities are assessed. Design: A comprehensive review was conducted using a thorough literature search of 5 online electronic databases (PubMed, PubMed Central, Cochrane, EMBASE, and Web of Science) from the time of their inception through March 2020. Studies evaluating gastric sleeve leaks were included. MeSH terms related to "endoscopic, " "leak, " "sleeve, " "gastrectomy, " "anastomotic, " and "bariatric" were applied to a highly sensitive search strategy. The main outcomes were epidemiology, pathophysiology, diagnosis, treatment, and outcomes. Results: Literature search yielded 2418 studies of which 438 were incorporated into the review. Shock and peritonitis necessitate early surgical intervention for leaks. Endoscopic therapies in acute and early leaks involve modalities with a focus on one of: (i) defect closure, (ii) wall diversion, or (iii) wall exclusion. Surgical revision is required if endoscopic therapies fail to control leaks after 6 months. Chronic leaks require one or more endoscopic, radiologic, or surgical approaches for fluid collection drainage to facilitate adequate healing. Success rates depend on provider and center expertise. Conclusion: Endoscopic management of leaks post sleeve gastrectomy is a minimally invasive and effective alternative to surgery. Their effect may vary based on clinical presentation, timing or leak morphology, and should be tailored to the appropriate endoscopic modality of treatment.